Efektivitas Surat Permintaan Penjelasan Data dan/atau Keterangan (SP2DK) Terhadap Penerimaan Pajak di KPP Pratama Ciamis - Isep Saepul Muzaki; Regi Refian Garis; Dede Abdul Rozak; Kasman Kasman (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Tax revenues are the largest revenue sector in the composition of the state budget in Indonesia. Taxes get a target of about 85% of all government revenues. The Directorate General of Taxes that has the mandate uses various instruments to be able to achieve tax revenues. One that is used in achieving tax revenues, The Directorate General of Taxes uses SP2DK. This study aims to determine the effectiveness of the request for an explanation of data and/or information (SP2DK) on tax revenues at the Tax Office Of Ciamis. The analytical method used is a descriptive method with a quantitative approach to give an idea of whether SP2DK has been effective or not. The data analysis technique used is descriptive. The results showed the effectiveness of SP2DK experienced fluctuations from 2016-2018, within 2016 of 0.03%, in 2017 of 9%, in 2018 of 8%. Overall, the SP2DK against Tax revenues in the Tax Office Of Ciamis is still ineffective. Under these conditions, the Head of Tax Office Of Ciamis must increase the effectiveness of the SP2DK issued.